A novel effector CfEC92 of Colletotrichum fructicola contributes to glomerella leaf spot virulence by suppressing plant defences at the early infection phase. (22nd April 2020) - Shang, Shengping; Wang, Bo; Zhang, Song; Liu, Guangli; Liang, Xiaofei; Zhang, Rong; Gleason, Mark L.; Sun, Guangyu
Abstract: The ascomycete fungus Colletotrichum fructicola causes diseases on a broad range of plant species. On susceptible cultivars of apple, it induces severe early defoliation and fruit spots, named glomerella leaf spot (GLS), but the mechanisms of pathogenicity have remained elusive. Phytopathogens exhibit small secreted effectors to advance host infection by manipulating host immune reactions. We report the identification and characterization of CfEC92, an effector required for C. fructicola virulence. CfEC92 is a Colletotrichum ‐specific small secreted protein that suppresses BAX‐triggered cell death in Nicotiana benthamiana . Accumulation of the gene transcript was barely detectable in conidia or vegetative hyphae, but was highly up‐regulated in appressoria formed during early apple leaf infection. Gene deletion mutants were not affected in vegetative growth, appressorium formation, or appressorium‐mediated cellophane penetration. However, the mutants were significantly reduced in virulence toward apple leaves and fruits. Microscopic examination indicated that infection by the deletion mutants elicited elevated deposition of papillae at the penetration sites, and formation of infection vesicles and primary hyphae was retarded. Signal peptide activity, subcellular localization, and cell death‐suppressive activity (without signal peptide) assays suggest that CfEC92 could be secreted and perform virulence functions inside plant cells. RNA sequencing and quantitative reverse transcription PCR results confirmed that the deletion mutants triggered elevated host defence reactions. Our results strongly support the interpretation that CfEC92 contributes to C. fructicola virulence as a plant immunity suppressor at the early infection phase. Abstract : The secreted protein CfEC92 of Colletotrichum fructicola suppresses BAX‐triggered programmed cell death in Nicotiana benthamiana and enhances pathogenicity on apple leaves and fruits by interfering with host resistance.